Anxiety Management through Coloring Play Therapy in a Preschool-Age Child during Hospitalization: A Nursing Case Study at RSUD dr. Gondo Suwarno Ungaran - Ayu Indah Nurcahyanti; Eka Adimayanti (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Preschool children are those aged 3 to 6 years. At this stage, their immune systems are not yet fully developed, making them more susceptible to health problems that may require hospitalization. Hospitalization often triggers anxiety due to separation from parents, invasive medical procedures that cause pain, and disruption of daily routines. If left unmanaged, anxiety may hinder the healing process and prolong the length of hospitalization. This case study aims to describe the nursing management of anxiety in a hospitalized preschool child through coloring play therapy. A descriptive case-study design was employed using the nursing care approach, comprising assessment, nursing diagnosis, intervention, implementation, and evaluation. Data were collected through interviews and observation, using a nursing assessment format and the Spence Children's Anxiety Scale (SCAS) questionnaire completed by the parent to measure the child's anxiety level. Coloring play therapy was provided for 20–30 minutes per session over three consecutive days to a preschool child experiencing anxiety during hospitalization for bronchopneumonia. After three days of nursing care, the results demonstrated a gradual reduction in the child's anxiety score, from 55 (severe) on day one to 39 (moderate) on day two and 15 (mild) on day three. The child appeared calmer, more cooperative, and better able to adapt to the hospital environment, indicating that the anxiety problem was successfully managed. It can be concluded that coloring play therapy is an effective nursing intervention for reducing anxiety in hospitalized preschool children. Nurses and families are encouraged to apply this activity to stimulate children's cognitive ability and fine motor skills, particularly during hospitalization.